DFT assessments of BN, AlN, and GaN decorated carbon cage scaffolds for sensing the thiamazole drug - Céspedes Panduro, Bernardo (2023)
Sensing drug substances by nanostructures are very important in accordance with the management of targeted drug delivery processes and drug substances detections. Boron nitride (BN), aluminum nitride (AlN), and gallium nitride (GaN) decorated carbon cage (BN-C, AlN-C, and GaN-C) scaffolds were assessed towards sensing the thiamazole (TMZ) drug through the wB97XD/6–31 + G* level of density functional theory (DFT) computations. The singular models were optimized and their combinations to each other were stabilized to obtain the interacting TMZ@Scaffold bimolecular complexes and their corresponding features. The results indicated the existence of non-covalent physical interactions between the substances and their electronic features indicated possibility of sensing function for the investigated scaffolds. Based on the variations of values of adsorption energy and energy gap, the features of recovery time and conductance rate were achieved to predict a sensing function for the models; TMZ@GaN-C was found at the highest suitability in comparison with TMZ@AlN-C and TMZ@BN-C models. The obtained thermochemistry results indicated a spontaneous process for the formation of TMZ@Scaffold complexes. Based on all the obtained results, an order of TMZ@GaN-C > TMZ@AlN-C >TMZ@BN-C was found for describing stability, formation, and electronic features suitability by assigning specific features for each of the singular BN-C, AlN-C, and GaN-C scaffolds towards the TMZ drug. As a consequence, two purposes of detections and adsorptions were approached for the investigated scaffolds to develop sensing functions of BN-C, AlN-C, and GaN-C scaffolds for the TMZ drug.